Preparation and Characterization of P-TSA Doped Tetraaniline Nanorods via Micellar-Assisted Method - K. Basavaiah; A. V. Prasada Rao (E-Journal of Chemistry)
In this work, we report preparation and characterization of P-toluene sulphonic acid (P-TSA) doped tetraaniline nanorods by micellar assisted method using ammonium per sulphate (APS) as an oxidant. Here, PTSA acts as dopant as well as template for tetraaniline nanostructures. The synthesized tetraaniline nanorods have been well characterized by Fourier transform infrared spectroscopy (FTIR), FT Raman spectroscopy, UV-Visible spectroscopy (UV-Visible), Scanning electron microscopy (SEM) and thermogravimetry. The morphologies of tetraaniline were found to be dependent on molar ratios of N-phenyl-1, 4-phenylenediamine (NPPD) to PTSA. The spectroscopic data indicated that PTSA doped tetraaniline nanorods. Thermogravimetry studies revealed that the PTSA doping improved the thermal stability of tetraaniline nanorods.